The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1084/jem.164.1.180
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for HLA-DR+ accessory cells in natural killing of cytomegalovirus-infected fibroblasts.

Abstract: The role of HLA-DR+ cells in NK activity against CMV-infected FS4 foreskin fibroblasts and K562 erythroleukemia cells was examined. When nonadherent PBMC were depleted of either HLA-DR+ or Leu-11b+ cells by treatment with mAbs plus C, NK activity against CMV-FS4 target cells was markedly reduced. In contrast, depletion of HLA-DR+ cells had no effect on NK activity against K562 target cells. When HLA-DR-depleted cells were added to Leu-11b-depleted cells, NK activity against CMV-FS4 was restored. Negative selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 29 publications
0
51
0
1
Order By: Relevance
“…pDC have been shown to be identical with the natural type I IFN producing cells, the rare HLA-DR-positive accessory cells that in human peripheral blood are responsible for type I IFN production in response to most viruses (7,8). The essential role of IFN-␣ produced by these HLA-DRpositive accessory cells for the cytolytic activity of NK cells against virus-infected target has been previously demonstrated (9) and these accessory cells have been differentiated from classical peripheral blood DC by conventional gradient separation methods. In this study we definitely discriminate the unique role of highly purified pDC in induction of cytolytic activity of NK cells in response to viral stimulation because the other population of HLA-DR-positive accessory cells in peripheral blood, myeloid DC, although very efficient in inducing cytolytic activity in cocultured NK cells in response to poly(I:C), do not induce cytolytic activity in response to virus.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…pDC have been shown to be identical with the natural type I IFN producing cells, the rare HLA-DR-positive accessory cells that in human peripheral blood are responsible for type I IFN production in response to most viruses (7,8). The essential role of IFN-␣ produced by these HLA-DRpositive accessory cells for the cytolytic activity of NK cells against virus-infected target has been previously demonstrated (9) and these accessory cells have been differentiated from classical peripheral blood DC by conventional gradient separation methods. In this study we definitely discriminate the unique role of highly purified pDC in induction of cytolytic activity of NK cells in response to viral stimulation because the other population of HLA-DR-positive accessory cells in peripheral blood, myeloid DC, although very efficient in inducing cytolytic activity in cocultured NK cells in response to poly(I:C), do not induce cytolytic activity in response to virus.…”
Section: Discussionmentioning
confidence: 98%
“…Cytolytic activity of NK cells has long been known to be enhanced by IFN-␣ (6), and type I IFN natural-producing cells (7), now known as pDC (8), have been shown to be required for NK cell-mediated lysis of virus-infected target cells (9). Mouse NK cells have also been shown to be activated by a DC cell line or by in vitro generated bone marrowderived DC and human NK cells by mature monocyte-derived DC (10 -15).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…Intracellular cytokine analysis in T cells were performed in primary MLR and in alloreactive T cells after repetitive stimulation with DCs. For use as responders, the primary MLR were set up with non-adherent PBMC (NPBMC) after depletion of HLA-DR + cells, B cells, NK cells [by mAb and complement-mediated lysis (Bandyopadhyay et al, 1986)], and allogeneic mature DCs were used as stimulators (1×10 6 NPBMC plus 1×10 5 DCs) in 24-well plates in 1 ml complete medium. Alloreactive T cells were expanded from primary culture with immature DCs from day 6 in the presence of 50 U/ml IL-2.…”
Section: Detection Of Intracellular Cytokines/chemokinesmentioning
confidence: 99%
“…These data suggest that NO affects the killing pathway after effector-to-target cell binding. It was reported that NK cell-mediated lysis of virus-infected cells required the production of IFN-by non-adherent accessory cells [10]. Inhibition of the production of IFN-by NO-releasing agents may affect NK activity against VZV-infected cells.…”
Section: Discussionmentioning
confidence: 99%